Die ontwikkeling van 'n strategiese gemeentelike ekklesiologie - op pad na 'n missionerende bedieningspraxis - G. Smit (Acta Theologica)
This article focuses on developing a theory of ministry praxis that moves from uniform  practices to the reflecting of diversity in a time of paradigm shift to the postmodern paradigm. Attention is paid to the ministry practices of the reformed tradition. A hermeneutic communicative ecclesiology of ministerial practices is used to describe the transfer from a single praxis to missionary ministry. The markers for this ecclesiology consist of Scripture metaphors referring to the church’s identity, her spiritual growth and her service in the Kingdom of God. In addition, these markers function on three levels: First, the level of God as the origin of the church; Secondly, the level of the church that recreates community with God through a life of gratitude and spiritual disciplines in the context of a family while functioning as a body of Christ; Thirdly, the level of the church’s relationship with God to the world by means of worship, gift-based ministry and testimony.